Blockchain Technology in Tourism : Enhancing Transparency and Security - Sirimavo Bandaranaike; Chandrika Kumaratunga; Ranil Wickremesinghe (International Conference On Digital Advanced Tourism Management And Technology, 2023)
Blockchain technology is emerging as a solution for improving transparency and security in the tourism sector. This paper investigates its applications in areas such as payment systems, identity verification, and supply chain management. The study highlights how blockchain can address issues like fraud, data privacy, and inefficiencies, fostering trust between stakeholders.